PEMBELAJARAN BAHASA ARAB MELALUI MODEL ROLE PLAYING DALAM MENINGKATKAN MAHARAH KALAM PADA SISWA KELAS X DI MA AL-HUSAINY KOTA BIMA - Dewi, Arnila Sari; Muslimin, Muslimin; Wahyuningsih, Sri (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2025)
Based on the findings and phenomena in the field or location that students find it easy to understand learning, this is evident when students speak in Arabic and because this role playing learning model involves students in class X as a whole where the main goal is that students can improve their speaking skills. This research uses qualitative research. Data collection techniques are observation, documentation and interviews. Data analysis techniques used are data reduction, data presentation and conclusion drawing. This research was conducted at MA Al-Husany Bima City which is located at Jln. Btn Pepabri No. 02 Lingk. Nusantara Monggonao Mpunda Bima City West Nusa Tenggara. Based on the results of the research conducted, the application of the role playing learning model significantly improves the Arabic maharah kalam (speaking ability) of class X students. This learning model provides an opportunity for students to interact directly with Arabic in realistic situations, which reduces awkwardness and increases their confidence when speaking.